Factors influencing brightness and beam quality of conventional and distributed Bragg reflector tapered laser diodes in absence of self-heating - Kaunga-Nyirenda, Simeon Newton; Bull, Stephen; Lim, Jun Jun; Hasler, Karl-Heinz; Fricke, Jörg; Larkins, Eric C. (Institution of Engineering and Technology, 2014)
In this study, the authors examine some of the factors affecting the brightness and the beam quality of high-power tapered lasers. The large volume resonators required to achieve a high-power, high-brightness operation make the beam quality sensitive to carrier lensing and a multimode operation. These cause bleaching of the regions outside the ridge waveguide. The beam quality in the conventional and the distributed Bragg reflector tapered lasers is examined in the absence of the self-heating effects to investigate the effect of the carrier lensing effects. The influence of the front facet reflectivity and the taper angle on the beam quality is investigated. The beam quality was found to degrade with an increase in the front facet reflectivity and for the larger taper angles in the conventional tapered lasers, especially at low ridge waveguide currents. Finally, the performance of the conventional tapered lasers employing a beamspoiler was assessed. The beam quality was found to be comparable with that achieved in the DBR tapered lasers.